Innovative Concept for the Implementation of Renewable Energy Sources in the Low-Carbon Economy Model In the light of surveys - Case Study Poland - Milena BERA (Communications of International Proceedings, 2025)
The implementation of innovations in the area of renewable energy sources (RES) is crucial in the promoted model of low-carbon economy. These innovations include the development of new technologies, such as more efficient photovoltaic cells and wind turbines, as well as the improvement of existing solutions, such as energy storage and smart grids. Therefore, the aim of the research is to present the current challenges related to the implementation of this innovative concept in the field of the low-carbon economy model. On this basis, the article presents selected results of surveys in the field of public awareness of the changes taking place in this area of RES with the acceptance of the development of these technologies. For the currently promoted model of low-carbon economy. The presented research may contribute to the faster development of utilitarian solutions for the implementation of this concept by identifying areas that, in the opinion of stakeholders – citizens, require identification or expansion of knowledge on this subject. In addition, the presented and interpreted results may provide a basis for the authorities responsible for shaping development policy in the currently promoted model of low-carbon economy by state authorities in Poland and the European Union.
Keywords: innovation; renewable energy sources; development policy; economic models